PLASMA EXCHANGE THERAPY (TPE) IN MYASTHENIC CRISIS PATIENTS - Prasetyo, Reza Fazri; Lubis, Bastian (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Myasthenic crisis is an acute exacerbation of myasthenia gravis that results in weakness of the respiratory muscles, potentially leading to acute respiratory failure and the necessity for mechanical ventilation support. Approximately 15-20% of individuals with myasthenia gravis will experience a myasthenic crisis at some point in their lives, making it one of the most dangerous and life-threatening complications if not addressed promptly. Fortunately, mortality rates associated with myasthenic crises are currently decreasing, partly due to the effectiveness of therapeutic plasma exchange (TPE). TPE therapy works by removing pathological antibodies, immune complexes, and cytokines from the plasma and replacing them with replacement fluid. In this report, we discuss the case of a 61-year-old man with myasthenia gravis who was admitted to the emergency department (ED) and then to the intensive care unit (ICU) for one day due to a myasthenic crisis. He was intubated and received mechanical ventilation support, followed by plasma exchange therapy, which resulted in clinical improvement.